(untitled) (Bangladesh Journal of Agricultural Research, 2011)
A survey was conducted in Jamalpur region to investigate the losses of pulses during storage at farmer’s level. It was observed that farmers used traditional methods for storing pulse crops. The containers, such as Jute bag with multiple (2-5) polythene lining inside (7.7% infestation), tin container with polythene lining inside by mixing sand with pulses (8.2% infestation), plastic container (7.8% infestation), plastic boium (8.6% infestation), and RC bottle (8.4% infestation) showed better performance for storing different pulse crops. The stored pulse of these containers had below 10% infestation level at low moisture content (below 10%) and high germination percentage (above 80%). In the study area, minimum number of farmers (1.81-3.45%) cultivated pulse crops since maximum arable lands were occupied by rice. Keywords: Pulse storage practices; assessment of losses; store insect infestation. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9246 BJAR 2011; 36(2): 205-212